?RESPONSE OF MAIZE (ZEA MAYS L.) TO ZINC AND PHOSPHORUS APPLICATION (Biological Sciences - PJSIR, 1995)
Pot and field experiments wereconducted to assess the response of maize (Zea mays L.) to Zinc application and the effect of Phosphorus on Zinc distribution in plants. It was observed that maize responded significantly (P